1, 3‐Diphosphacyclobutene Cobalt Complexes. Issue 24 (8th April 2019) - Rödl, Christian; Schwedtmann, Kai; Weigand, Jan J.; Wolf, Robert
Abstract: The synthesis and characterization of rare 1, 3‐diphosphacyclobutene transition‐metal complexes is described. Reactions of the cobalt‐hydride complex [Co(P2 C2 t Bu2 )2 H] (G ) with n BuLi, t BuLi, or PhLi afforded [Li(solv) x Co(η 3 ‐P2 C2 t Bu2 HR)(η 4 ‐P2 C2 t Bu2 )] (1 : R= n Bu, (solv) x =(Et2 O)2 ;2 : R= t Bu, (solv) x =(thf)2 ;3 : R=Ph, (solv) x =(Et2 O)(thf)2 ), with an η 3 ‐coordinated 1, 3‐diphosphacyclobutene ligand as a result of organyl‐anion attack at one of the phosphorus atoms of the bis(1, 3‐diphosphacyclobutadiene) backbone. In contrast to the reactions with PhLi, the aryl‐magnesium compounds p ‐tolyl magnesium chloride and p ‐fluorophenyl magnesium bromide deprotonate [Co(P2 C2 t Bu2 )2 H] to give the magnesium salt [Mg(MeCN)6 ][Co(η 4 ‐P2 C2 t Bu2 )2 ]2 (4 ), which contains a bis(1, 3‐diphosphacyclobutadiene)‐cobaltate anion. The [Co(η 4 ‐P2 C2 t Bu2 )2 ] − anions are well separated from the octahedral [Mg(MeCN)6 ] 2+ cation in the molecular structure of4 . Compound1 reacts with Me3 SiCl to give neutral [Co(η 3 ‐P2 C2 t Bu2 H n Bu)(η 4 ‐P2 C2 t Bu2 SiMe3 )] (5, 52 % yield) with an SiMe3 group attached to one of the P atoms of the previously unfunctionalized backbone. Abstract : Addition of lithium organyls (R−Li) to a phosphaorganometallic hydride complex is a simple and effective route to metal complexes with unprecedented η 3 ‐1, 3‐diphosphacyclobutene ligands. Diastereomeric products were isolated depending on reaction conditions and the nature of the organic nucleophile (R=alkyl versus aryl). The complexes were further functionalized by reaction with Me3 SiCl.